Risk Factors for Persistent or Recurrent Central Serous Chorioretinopathy - Jia Yu; Gezhi Xu; Qing Chang; Xiaofeng Ye; Lei Li; Chunhui Jiang; Qi Zhao (Journal of Ophthalmology)
Purpose. To investigate the risk factors for persistent or recurrent central serous chorioretinopathy (CSC). Materials and Methods. Consecutive treatment-naïve CSC patients were included from January 2017 to October 2018. All patients were asked to complete questionnaires, addressing previously described risk factors for the development of CSC. Patients were divided into two groups: those with acute CSC, who were in the first episode, with spontaneous resolution of subretinal fluid within 3 months, and with no recurrence within 1 year; and those with persistent or recurrent CSC, the remaining patients. Results. In total, 138 patients were enrolled: 20 (14.5%) with acute CSC and 118 (85.5%) with persistent or recurrent CSC. Using multivariate analysis, male sex (odds ratio (OR), 95% confidence interval: 5.63 [1.02–31.02]; p=0.047), older age (OR: 1.14 [1.03–1.25]; p=0.008), and higher Insomnia Severity Index score (OR: 1.30 [1.05–1.60]; p=0.015) were found to be independently associated with persistent or recurrent CSC. Conclusions. Male sex, age, and sleep disorders are risk factors for persistent or recurrent CSC in the natural history. These patients may require early photodynamic therapy. Treatment for sleep disorders is strongly recommended. All CSC patients may require careful and periodic follow-up.